Debt levels, debt composition, and sovereign spreads in emerging and advanced economies - Salvatore Dell'Erba; Ricardo Hausmann; Ugo Panizza (Graduate Institute of International and Development Studies, 2013)
This paper studies the relationship between sovereign spreads and the interaction between debt composition and debt levels in advanced and emerging market countries. It finds that in emerging market countries there is a significant correlation between spreads and debt levels. This correlation, however, is not statistically significant in countries where most public debt is denominated in local currency. In advanced economies, the magnitude of the correlation between debt levels and spreads is about one fifth of the corresponding correlation for emerging market economies. In Eurozone countries, however, the correlation between spreads and debt ratios is similar to that of emerging market countries. The paper also shows that the financial crisis amplified the relationship between spreads and debt levels within the Eurozone but had no effect on the relationship between spreads and debt in standalone countries. Finally, the paper shows that the relationship between debt levels and spreads is amplified by the presence of large net foreign liabilities. This amplifying effect of net foreign liabilities is larger in the Eurozone than in standalone advanced economies. The paper concludes that debt composition matters and corroborates the original sin hypothesis that, rather than being a mere reflection of institutional weaknesses, the presence of foreign currency debt increases financial fragility and leads to suboptimal macroeconomic policies.
Keywords: H63; F33; 330; spreads; public debt; original sin; Euro